(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
In a rapidly changing competitive world, the success ofany organization will depend heavily on its ability to meet demands and respondquickly to fluctuations and change. In this fashion conscious world, whereinconsumers are keenly interested in different styles for each new season hasclearly shifted to the future of the Indian garment exports. So the Indiangarment exporters slowly and steadily following global trends of supply chaincollaboration and developed a set of strategies to manage them as a resultseveral of the world’s leading fashion brands are sourcing products from India. With the phasing out of the Multi Fibre Agreement (MFA)in 2005 the world garment industry was put on one platform where the countrieshad to compete with each other to grab business. On the one hand work pressurehas been constantly rising while on the other working conditions in thefactories are going from bad to worse. While the garment industry is one of thebiggest sources of export, with considerable and rapid increase in growth,there has been a corresponding race to the bottom in so far as labour standardsand wages are concerned. A competitive pressure has substantially increased atmost of the levels, customer is supposed to get better offer and value for hismoney offers. This will definitely makes customer more satisfied. The Indian garmentindustry is a major source of employment and foreign exchange contributes to 4%of the country’s GDP and 14% of its industrial output. This industry being thesecond largest employer provides jobs to around 35 million people play anextremely significant role in terms especially of share in value added, foreignexchange earnings, and employment. There is a tremendousopportunity for export of garment products. However, our country has not beenable to convert this potential into reality, mainly due to the lack of marketcompetitiveness, technical up-gradation, operational efficiency and increase ininput cost and so on; as a result India’s presence is felt only in the lowvalue segment. In the view of above problems, this article highlights various issuesof export, competitive pressure, recent trends in customers satisfaction, Govt.support etc. of garment sector in Karnataka.